Zastosowanie teorii performansu Diany Taylor w badaniach nad kultem Świętej Śmierci w Meksyku - Kaleta, Karolina I. (Humaniora. Czasopismo Internetowe, 2023)
The aim of the article is to analyse the latest trends in Mexican cult of Santa Muerte (the Saint Death) using the terms proposed by Diana Taylor in her theory of performance. The concepts of the archive and the repertoire are especially functional for describing contemporary hybrid religious phenomena which undergo constant transformations and which origins are diverse. Application of mentioned terms permits to capture the sources of those metamorphoses and their religious and cultural background. This allows to demonstrate how the unrelated archives convert into the repertoire of practices connected with the cult of the Saint Death. These practices are not limited only to the ones representing strictly religious character but they include various activities – performances of everyday life – for which Santa Muerte is a certain type of context, background or reference point.